2000
DOI: 10.1006/bbrc.1999.2015
|View full text |Cite
|
Sign up to set email alerts
|

Internalization and Processing of Human Angiogenin by Cultured Aortic Smooth Muscle Cells

Abstract: Human angiogenin is a 14-kDa plasma protein with angiogenic and ribonucleolytic activities. Angiogenin binds specifically to aortic smooth muscle cells, activates second messenger pathways, and inhibits their proliferation. Human and bovine aortic smooth muscle cells were used to study the internalization and intracellular fate of human angiogenin at 37 degrees C. Using a specific antibody against angiogenin, we found that the internalized native protein was localized in the perinuclear region at 30 min and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The majority of the circulating ANG is produced by the liver (29). Moreover, with a seeming fast turnover rate and a half-life of 2 h (30), a large quantity of ANG inhibitors would be needed to neutralize the circulating ANG.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the circulating ANG is produced by the liver (29). Moreover, with a seeming fast turnover rate and a half-life of 2 h (30), a large quantity of ANG inhibitors would be needed to neutralize the circulating ANG.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the circulating ANG is produced by the liver [23]. Moreover, with a seemingly fast turnover rate and a half-life of 2 h [34], a large quantity of ANG inhibitors would be needed to neutralize the circulating ANG.…”
Section: Ang As a Molecular Target For Prostate Cancer Drug Developmentmentioning
confidence: 99%
“…In order to reach the nucleus, a secreted protein has to be internalized back to the cytoplasm or, in the case of IPSE/alpha-1, into the cytoplasm of host cells. This may involve endocytosis-dependent processes, as reported for angiogenin (23) and parathyroid hormone-related protein (PtHrP) (3). Using standard approaches, we have demonstrated that IPSE/alpha-1 contains a monopartite functional NLS motif (PKRRRTY) that is necessary and sufficient for its translocation to the nucleus.…”
mentioning
confidence: 99%